Macronutrient concentrations in stems of red pitahaya [Hylocereus undatus (Haw.) Britton and Rose] in Ecuador - Palacios, Christian Mauricio (2025)
The white-fleshed red pitahaya (Hylocereus undatus (Haw.) Britton and Rose) is a perennial cactus with relevance in the international fruit trade, due to its physical and nutritional characteristics. This research provides information on macronutrient concentrations in pitahaya stems, based on stem samples from six production sites with different plant densities (low and high). A completely randomized design with five replicates in each treatment was employed. The results revealed significant differences in macronutrient concentrations between production sites and plant densities. The most relevant nutrients were potassium, calcium and nitrogen. The mean potassium concentration among production sites was 3.82% on dry matter, while for calcium it was 2.91% and nitrogen 1.12%. The maximum concentrations of potassium and nitrogen were recorded in San Jacinto (6.58 and 1.72%, respectively) and that of calcium in San Eloy (5.65%). In addition, the results analyzed between densities showed that the highest accumulation of nutrients in the stems occurred in the low planting density zone. These results are the first reported in Ecuador and establish a reference for crop management, particularly in nutritional diagnosis for the efficient use of resources and soil preservation.